I think that she is wrong as if a power is outside of a bracket, the result could be very different compared to when the power is inside the bracket.

I think she is correct as 5x2* is equal to 5x [ (x)(x) ] and (-5x)2 is equal to (5x5) + [ (x)(x) ]

She is wrong. So (-5x)^2 = -5x times -5x ( Negative times Negative = Positive rule ) = 25x And (5x)^2 = 5x times 5x = 25x

I think that she is wrong as if a power is outside of a bracket, the result could be very different compared to when the power is inside the bracket.

ReplyDeleteI think she is correct

ReplyDeleteas 5x2* is equal to 5x [ (x)(x) ]

and (-5x)2 is equal to (5x5) + [ (x)(x) ]

She is wrong. So (-5x)^2 = -5x times -5x ( Negative times Negative = Positive rule )

ReplyDelete= 25x

And (5x)^2 = 5x times 5x

= 25x